2014
DOI: 10.1016/j.neuropharm.2014.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal melanocortin receptor agonist treatment reduces play fighting and promotes adult attachment in prairie voles in a sex-dependent manner

Abstract: The melanocortin receptor (MCR) system has been studied extensively for its role in feeding and sexual behavior, but effects on social behavior have received little attention. α-MSH interacts with neural systems involved in sociality, including oxytocin, dopamine, and opioid systems. Acute melanotan-II (MTII), an MC3/4R agonist, potentiates brain oxytocin (OT) release and facilitates OT-dependent partner preference formation in socially monogamous prairie voles. Here we examined the long-term impact of early-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 85 publications
1
32
0
Order By: Relevance
“…In the context of the starvation, decreasing prosocial behavior in favor of feeding behaviors is appropriate, and consistent with animal studies (Barrett et al, 2014). Examination of the methylation status of risk genes in psychiatric illness may provide an additional indicator of gene expression (Hing et al, 2014).…”
Section: Discussionsupporting
confidence: 70%
“…In the context of the starvation, decreasing prosocial behavior in favor of feeding behaviors is appropriate, and consistent with animal studies (Barrett et al, 2014). Examination of the methylation status of risk genes in psychiatric illness may provide an additional indicator of gene expression (Hing et al, 2014).…”
Section: Discussionsupporting
confidence: 70%
“…Repeated OXT treatments during the first postnatal week increase the number of isolation-induced ultrasonic vocalizations (60), a measure of social vocal communication. In addition, daily neonatal treatment during this first week of life with a selective MC4R agonist promotes adult partner preference (61). Similarly, in mice, a single postnatal administration of OXT at P1 facilitated alloparental care and social approach in adulthood, while administration of an OXT antagonist produced the opposite effect (62) and sub-chronic OXT treatment in juvenile rats has long lasting effects in social behavior, which is accompanied by increased plasma OXT levels (63).…”
Section: Discussionmentioning
confidence: 99%
“…Human studies have demonstrated that polymorphisms in the OXTR gene interact with early life adversity to predict quality of mothering and postpartum mood (Mileva-Seitz et al, 2013), in addition to adult emotion regulation and attachment style (Bradley et al, 2011). Experimental studies have demonstrated that OT circuits are sensitive to early social context, and early-life manipulation of these systems have long-term effects on later life social attachment behaviors (Ahern and Young, 2009; Ahern et al, 2011; Barrett et al, 2014). More recently, individual variation in NAcc OXTR density has been shown to interact with early-life social experiences to influence the ability to form partner preferences in adult prairie voles (Barrett et al, Under Revision).…”
Section: Discussionmentioning
confidence: 99%